Physical Activity, Obesity, and Hypertension among Adults in a Rapidly Urbanised City - Qianqian Dun; Wanglin Xu; Maozhen Fu; Nengjian Wu; Justin B. Moore; Ting Yu; Xin Li; Yating Du; Biao Zhang; Qiaomai Wang; Yiting Duan; Ziqi Meng; et al. (International Journal of Hypertension)
Background. Few studies have explored the relationship between the level of physical activity and the occurrence or prevalence of obesity and hypertension among people residing in urbanised areas. Method. A cross-sectional study involving a sample of 1,001 adults was conducted. Descriptive statistics were used to describe sociodemographic variables, physical activity levels, body mass index (BMI), and prevalence of hypertension. Logistic regression models were adopted to investigate the relationship between these factors. Results. A total of 939 respondents who provided valid responses were included. Among them, 56.5% of the participants reported engaging in high levels of physical activity. However, 40.4% of the respondents were classified as overweight or obese, and 31.9% had diagnosed hypertension. After adjusting for sociodemographic factors, logistic regression analysis revealed that physical activity levels were negatively correlated with the prevalence of BMI (OR = 0.564, 95% CI: 0.352–0.905; OR = 0.583, 95% CI: 0.375–0.907) and hypertension (OR = 0.556, 95% CI: 0.348–0.888). Conclusions. Our study confirms recent evidence regarding the amount of physical activity that is associated with lower prevalence of obesity and hypertension in Pingshan District. Furthermore, different physical activities of various intensity levels had different effects on hypertension. Residents should be encouraged to engage in physical activities and maintain a healthy weight to improve their quality of life.